2012
DOI: 10.1093/infdis/jis400
|View full text |Cite|
|
Sign up to set email alerts
|

Relative Contributions of Macrovascular and Microvascular Dysfunction to Disease Severity in Falciparum Malaria

Abstract: Vital organ dysfunction in severe malaria results primarily from sequestration of parasitized erythrocytes in the microvasculature rather than reduction in circulating blood volume and oxygen delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
70
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(73 citation statements)
references
References 31 publications
2
70
0
1
Order By: Relevance
“…8 Recent studies have shown that liberal fluid resuscitation does not improve acid-base balance and renal function in severe falciparum malaria, whereas inappropriate fluid replacement may exacerbate pulmonary edema. 10,11 Of importance, acute renal injury in severe falciparum malaria seems to result from pathological processes associated with parasitized erythrocytes sequestered in microcirculation. Although it is unknown whether macrovascular fluid depletion or microvascular sequestration of parasitized erythrocytes primarily contribute to acute renal injury in knowlesi malaria, artesunate treatment but not fluid resuscitation lead to rapid recovery of renal function in severe falciparum malaria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Recent studies have shown that liberal fluid resuscitation does not improve acid-base balance and renal function in severe falciparum malaria, whereas inappropriate fluid replacement may exacerbate pulmonary edema. 10,11 Of importance, acute renal injury in severe falciparum malaria seems to result from pathological processes associated with parasitized erythrocytes sequestered in microcirculation. Although it is unknown whether macrovascular fluid depletion or microvascular sequestration of parasitized erythrocytes primarily contribute to acute renal injury in knowlesi malaria, artesunate treatment but not fluid resuscitation lead to rapid recovery of renal function in severe falciparum malaria.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is unknown whether macrovascular fluid depletion or microvascular sequestration of parasitized erythrocytes primarily contribute to acute renal injury in knowlesi malaria, artesunate treatment but not fluid resuscitation lead to rapid recovery of renal function in severe falciparum malaria. 10,11 Meanwhile, jaundice seems to be a common feature observed in renal failure in severe malaria and mainly stems from acute hemolysis that could further compromise renal function. 8,12,13 Despite the rarity of overt liver failure in malaria, transient disturbance of hepatic function is not uncommon.…”
Section: Discussionmentioning
confidence: 99%
“…The blockage of small diameter vasculature may be directly observed in vivo in the retinal veins of children with CM, and in the mucous membranes of adults with CM [15,20]. Although there have been no studies directly observing cerebral blood vessels during life, post-mortem samples show high levels of sequestration in brain vasculature [12].…”
Section: Pathogenesismentioning
confidence: 99%
“…parasites that infect humans. Its ability to cytoadhere and sequester itself in the microvasculature can result in obstruction of blood flow and organ dysfunction, and these are key processes in the development of severe falciparum malaria (1).…”
mentioning
confidence: 99%